Susceptibility of peaches to Taphrina deformans in relation to blooming, environmental factors and genetic inheritance - S.D. BADIYALA, I.M. SHARMA and (Indian Phytopathology, 2002)
During 1988, 1989 and 1990, thirty two peach cultivars were evaluated for their susceptibility to peach leaf curl (Taphrina deformans). None of the peach cultivars were immune. However, cultivars Bed Will's Early, July Elberta and World's Earliest showed tolerant reaction irrespective of congenial environmental conditions, whereas eight cvs., namely, Florida Red, Early Amber, Sharbati, 16-33, Sun Gold, Sun Red, Florida Sun and Foster were highly susceptible. The early blooming cultivars were observed to be highly susceptible to peach leaf curl infection but the varieties with longer incubation period were found resistant, which suggests that suceptibility is heritable.